Blok atrioventrikel pada bayi: sebuah laporan kasus - Cahyono, Agus (The Indonesian Heart Association, 2022)
Background: Atrioventricular (AV) block in children may pose a challenge for phycisians. However, it can be detected with careful physical examination. Case illustration: A 4 month old infant presented with bradycardia that did not improve during observation period. Her electrocardiography (ECG) showed complete atrioventricular block and her echocardiography showed secundum atrial septal defect (ASD) and patent ductus arteriosus (PDA). Her father’s ECG showed first degree AV block. She was recovered well after pacemaker implantation and PDA ligation. Conclusion: An infant who suffered from complete AV block was successfully treated with pacemaker.This article has a related Erratum.